Characterization of LysBM1, a novel high-penetrating phage lysin targeting enterohemorrhagic Escherichia coli - Liu, Haitao; Sun, Lichang; Sun, Quan; Zhang, Shiqiang; Wang, Ran (Frontiers in Veterinary Science, 2025)
We investigated the lytic activity of the bacteriophage endolysin (lysin) LysBM1, which has a predicted molecular mass of ~25 kDa and is encoded by an enterohemorrhagic Escherichia coli (EHEC) phage. LysBM1 was over expressed in Pichia pastoris GS115 and purified protein exhibited optimal bactericidal activity in vitro. Herein, the antimicrobial and penetrating activity of LysBM1 were studied. Our results showed that the lysin displayed a broad lytic spectrum and high activity, with in vitro treatment killing all 21 of the clinical EHEC strains tested. Laser confocal microscopy showed Alex Fluor 610-X conjugate-labelled LysBM1 inside EHEC E5 cells, while confocal laser scanning microscopy revealed that cells exposed to LysBM1 for 5 min suffered deformation and disruption of the cell wall. A LysBM1 protein containing mutations within the active sites (LysBM1-M) retained bactericidal activity despite its inability to hydrolyze peptidoglycan. Both LysBM1 and LysBM1-M could penetrate the E. coli outer membrane, confirming that LysBM1 had membrane-disrupting activity. The present results suggest that LysBM1 has the potential to be used as an alternative therapeutic agent against pathogenic EHEC strains.